Preparation of ferrocene‐based Schiff base derivatives for the thermal decomposition of ammonium perchlorate. Issue 2 (3rd December 2022) - Liu, Jinyi; Yu, Haojie; Wang, Li; Vatsadze, Sergey Z.; Huang, Zhikun; Li, Xuefei; Ding, Lei
Abstract: Ammonium perchlorate (AP) is a common oxidizer and accounts for over 60 wt% in composite solid propellants (CSPs). Ferrocene (Fc)‐based compounds have become one of the most widely used burning rate catalysts (BRCs) for AP decomposition due to their outstanding catalytic effect. To improve the anti‐migration ability of Fc‐based compounds during long‐time storage, seven Fc‐based Schiff base derivatives were synthesized. Their molecular structures were characterized by UV‐Vis, FT‐IR, 1 H NMR, 19 F NMR, ESI‐MS and EA. Meanwhile, their electrochemical behaviors and catalytic effects for AP decomposition were studied by CV and TG techniques. The results showed that these synthesized compounds had good catalytic effect, obviously reducing the thermal decomposition temperature of AP. Moreover, their anti‐migration properties were also investigated by the aging test of simulated propellant. The results showed that they had better anti‐migration ability than commercial BRCs (catocene, Cat ). This study demonstrates that Fc‐based Schiff base compounds are possible BRCs for AP‐based propellant. Abstract :